ANALISIS PERLAKUAN AKUNTANSI ASET TETAP / BARANG MILIK DAERAH ALAT BESAR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SAMBAS - Eliza Noviriani (Sebi : Studi Ekonomi dan Bisnis Islam, 2021)
Analysis of Accounting Treatment of Fixed Assets/Regional Property Large Tools of the Public Works and Spatial Planning Office of Sambas Regency. This research aims to find out how the accounting treatment of fixed assets especially large equipment tools at the Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Sambas in 2020. The main reason why to do this research is researcher sees there’s many several large equipment tools that becomes wrecked and abandoned, so the researcher raises this title of research for scription. Type of this research is qualitative with a transcendental phenomenology approach, for the data used are primary data obtained directly from data sources and interviews result, and for secondary data obtained indirectly such as journals, books, and Government Regulation Number 71 of 2010. Data collecting’s techniques using interviews, observation, and documentation. Analysis of the treatment of fixed assets especially large equipment tools is used by refer to Government Regulation Number 71 of 2010 concerning Statement of Government Accounting Standard Number 07 about the treatment of fixed assets, Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Sambas for treatment of fixed assets especially large equipment tools has been fully referred to Government Regulation Number 71 of 2010 concerning Statement of Government Accounting Standard Number 07.